Image encryption method for depth + texture video contents. (18th March 2015) - Choi, Hyunjun
This paper proposes a contents security technique for digital holographic display systems. A digital holographic display system assumes that it follows faithfully the current system frame in processes such as image acquisition, processing, transmission, reception and reconstruction to provide 2D or 3D video services. For the image acquisition in this system, RGB and depth cameras are used. An image contents encryption technique, which is executed in the digital holographic display system, is proposed. This technique encrypts only a part of data by performing the frequency transformation of depth-maps and RGB images. In this paper, two applications of the proposed encryption technique are discussed. In the first one, only depth-maps are encrypted and in the second one, depth-maps and RGB image information are encrypted simultaneously. The experiment results reveal that 0.73% of the entire data are encrypted and that the proposed technique can effectively hide the visual information of an original RGB image and depth-map.